A critique on the micromachining of steel. (11th May 2010) - Jackson, Mark J.; Novakov, Tamara
A critique on some recent computational results on the subject of micromachining of steel is presented in this paper. A scientific-based criticism is presented of selected results and analysis on the nature of chip formation at the microscale. The paper confirms that a mechanism known as 'quasi-shear extrusion' takes place when machining materials of variable hardness and is confirmed using a dedicated finite element model for the analysis of machining at the microscale. The authors also provide an insight into how to further investigate the phenomenon of 'quasi-shear extrusion chip formation' from an experimental viewpoint.